Brain serotonin 4 receptor binding is inversely associated with verbal memory recall. Issue 4 (17th March 2017) - Stenbæk, Dea S.; Fisher, Patrick M.; Ozenne, Brice; Andersen, Emil; Hjordt, Liv V.; McMahon, Brenda; Hasselbalch, Steen G.; Frokjaer, Vibe G.; Knudsen, Gitte M.
Abstract: Background: We have previously identified an inverse relationship between cerebral serotonin 4 receptor (5‐HT4 R) binding and nonaffective episodic memory in healthy individuals. Here, we investigate in a novel sample if the association is related to affective components of memory, by examining the association between cerebral 5‐HT4 R binding and affective verbal memory recall. Methods: Twenty‐four healthy volunteers were scanned with the 5‐HT4 R radioligand [ 11 C]SB207145 and positron emission tomography, and were tested with the Verbal Affective Memory Test‐24. The association between 5‐HT4 R binding and affective verbal memory was evaluated using a linear latent variable structural equation model. Results: We observed a significant inverse association across all regions between 5‐HT4 R binding and affective verbal memory performances for positive ( p = 5.5 × 10 −4 ) and neutral ( p = .004) word recall, and an inverse but nonsignificant association for negative ( p = .07) word recall. Differences in the associations with 5‐HT4 R binding between word categories (i.e., positive, negative, and neutral) did not reach statistical significance. Conclusion: Our findings replicate our previous observation of a negative association between 5‐HT4 R binding and memory performance in an independent cohort and provide novel evidence linking 5‐HT4 R binding, as a biomarker for synaptic 5‐HT levels, to the mnestic processing of positive and neutral word stimuli in healthy humans. Abstract : We here present novel evidence of a significant inverse relation between cerebral serotonin 4 receptor (5‐HT4R) binding and affective memory performances in healthy volunteers. These findings support the relevance of 5‐HT4R in relation to affective components of memory and provide insight into molecular mechanisms that may contribute to the risk architectures for affective disorders and antidepressants effects.